Optimisation of the design of infrastructure components subject to progressive deterioration and extreme loads - Sanchez-Silva, Mauricio; Klutke, Georgia-Ann; Rosowsky, David V. (Structure and infrastructure engineering, 2012)
The construction of new infrastructure requires solutions that maximise the benefit while meeting acceptable safety levels. The solution to this problem can be obtained through a structural cost-based optimisation. This paper integrates a life-cycle cost optimisation model developed by Rackwitz ( 2000 ) with a structural deterioration model that combines the action of progressive degradation (e.g. corrosion, fatigue) and sudden events (e.g. earthquakes). The structural condition at a given time is measured in terms of the system's remaining life, which can be measured in practice through any structural performance indicator (e.g. ductility). It is assumed that sudden events conform to a compound point process with shock sizes and interarrival times that are independent and identically distributed random variables. Deterministic and random progressive deterioration models are also included in the formulation. Randomness in progressive deterioration is modelled as a point process with known arrival times and random shock sizes. Structural reliability is evaluated against prescribed design and operation thresholds that can be used to establish limit states or intervention policies. The entire model is illustrated with an example that compares several life-cycle models showing the importance of taking into account the damage history in evaluating the performance of infrastructure systems.